Tectonic rotations and internal structure of Eocene plutons in Chuquicamata, northern Chile - Somoza, Ruben (2015)
A paleomagnetic and AMS study on Eocene plutonic complexes in the Calama area, northern Chile, reveals high-temperature, high-coercivity magnetizations of dominantly thermoremanent origin and magnetic fabrics controlled by magnetite. The paleomagnetic results indicate that ~ 43Ma plutons underwent clockwise tectonic rotation, whereas adjacent ~ 39Ma plutons did not undergo discernible rotation. This points to a middle Eocene age for the younger tectonic rotations associated with the Central Andean Rotation Pattern in the Chuquicamata-Calama area.